Long-term outcome of microwave ablation for benign thyroid nodules: Over 48-month follow-up study - Du, Jia-Rui; Li, Wen-Hui; Quan, Cheng-Hai; Wang, Hui; Teng, Deng-Ke (Frontiers in Endocrinology, 2022)
Objectives The short-term effects of microwave ablation (MWA) for the treatment of benign thyroid nodules (BTNs) were satisfactory in previous studies. However, as a slowly progressing disease, the long-term efficacy of MWA for BTNs at present is not clear. Our study aim was to assess the long-term results of MWA for BTNs after a 48-month follow-up. Methods From June 2015 to September 2017, 148 patients had 148 BTNs. All patients were from the China-Japan Union Hospital of Jilin University. Careful ultrasound examinations were performed 1 day, 1 month, 3 months, 6 months, 12 months, and every 6 months after MWA. The volume, volume reduction rate (VRR), recurrence rate of the ablated area and thyroid function were recorded. Results The mean volumes of the 148 nodules were 15.6 ± 9.4 cm3 (range: 1.3-48.9 cm3) and 0.6 ± 0.6 cm3 (range: 0-3.5 cm3) before and 48 months after MWA, respectively, with a nodule VRR of 96.9 ± 2.5% (range: 90.4-100%). Two patients (1.35%) had recurrence after MWA. Compared with thyroid function before MWA, no significant variation was observed after MWA. Five patients experienced complications (3.38%): two patients (1.35%) had bleeding, two patients (1.35%) had ear pain and toothache during MWA, and one patient (0.68%) had hoarseness after MWA. No cases of oesophageal injury, tracheal injury, infection, skin burns, etc., were reported during or after MWA. Conclusions Based on a long-term follow-up, MWA is an effective method for treating BTNs and is expected to be a potential first-line treatment.